Comparative characteristics of the clinical application of the latest fixing gels for complete dentures - Shuturminskyi Віталій Григорович; Seredynko Ігор Анатолійович (Actual Dentistry, 2020)
The purpose of this study is to determine their effectiveness and benefits based on a comparative analysis of the most common adhesive systems on the market. Materials and methods. The clinical efficacy of adhesive compositions in patients with full dentition of the mandible with complex anatomic-functional conditions of the prosthetic bed was studied. Patients used fixing gels immediately after denture application. In group 1, patients used PresiDENT gel (Betafarma SpA), in group 2 patients used Protefix cream (Queisser Phrma), patients in group 3 used Lacalut dent cream (Dr. Theiss Naturvagen GmbH), group 4 included patients who used the cream Corega Comfort (GSK). It was used for clinical evaluation of functionality method of N.M. Urazaeva. To evaluate the fixation of complete removable dentures on the lower jaw used a modified test by T. Mirsayev. Results. In the study of chewing efficiency, it was found that when applying adhesive creams the period of chewing was reduced, especially significantly – when applying the «Corega Comfort» adhesive (by 40 %), the decrease in the amount of movement decreased by 46.1 %) (p < 0,05). With long-term use, the Corega Comfort adhesive cream has improved its chewing efficiency by 14.3 %. It should be noted that the chewing efficiency did not improve over time withthe Lacalut dent adhesives. High level of improvement was observed with the use of Protefix cream (by 16.6%). Conclusions. All adhesives contribute to the improvement of chewing efficiency: the period of chewing was reduced, especially significantly – with the use of «Corega Comfort» adhesive (by 40 %), the decrease in the number of movements before swallowing decreased by 46.1 %) (p < 0.05). With long-term use, the Corega Comfort adhesive cream has improved its chewing efficiency by 14.3 %. It should be noted that the chewing efficiency did not improve over time with the Lacalut dent adhesives. High level of improvement was observed with the use of Protefix cream (by 16.6%). The use of adhesive systems with full removable prosthetics significantly improves the fixing force from 45.9 %", when using the adhesive "Corega Comfort" to 104,9 %.